Predicting Deformity Correction of Growth Modulation in Late-onset Tibia Vara. Issue 5 (13th May 2023) - Walker, Janet L.; Dueber, David M.; Powell, Kenneth P.; Stephenson, Lindsay P.; Scott, Allison C.; Lerman, Joel A.; Nossov, Sarah B.; Franklin, Corinna C.; Westberry, David E.
Abstract : Background: Growth modulation in late-onset tibia vara (LOTV) has been reported to yield variable results. We hypothesized that parameters of deformity severity, skeletal maturity, and body weight could predict the odds of a successful outcome. Methods: A retrospective review of tension band growth modulation for LOTV (onset ≥8 y) was performed at 7 centers. Tibial/overall limb deformity and hip/knee physeal maturity were assessed on preoperative anteroposterior standing lower-extremity digital radiographs. Tibial deformity change with first-time lateral tibial tension band plating (first LTTBP) was assessed by medial proximal tibia angle (MPTA). Effects of a growth modulation series (GMS) on overall limb alignment were assessed by mechanical tibiofemoral angle (mTFA) and included changes from implant removal, revision, reimplantation, subsequent growth, and femoral procedures during the study period. The successful outcome was defined as radiographic resolution of varus deformity or valgus overcorrection. Patient demographics, characteristics, maturity, deformity, and implant selections were assessed as outcome predictors using multiple logistic regression. Results: Fifty-four patients (76 limbs) had 84 LTTBP procedures and 29 femoral tension band procedures. For each 1-degree decrease in preoperative MPTA or 1-degree increase in preoperative mTFA the odds of their successful correction decreased by 26% in the first LTTBP and 6% by GMS, respectively, controlling for maturity. The change in odds of success for GMS assessed by mTFA was similar when controlling for weight. Closure of a proximal femoral physis decreased the odds of success for postoperative-MPTA by 91% with first LTTBP and for final-mTFA by 90% with GMS, controlling for preoperative deformity. Preoperative weight ≥100 kg decreased the odds of success for final-mTFA with GMS by 82%, controlling for preoperative mTFA. Age, sex, race/ethnicity, type of implant, and knee center peak value adjusted age (a method for bone age) were not predictive of outcome. Conclusions: Resolution of varus alignment in LOTV using first LTTBP and GMS, as quantified by MPTA and mTFA, respectively, is negatively impacted by deformity magnitude, hip physeal closure, and/or body weight ≥100 kg. The presented table, utilizing these variables, is helpful in the prediction of the outcome of the first LTTBP and GMS. Even if complete correction is not predicted, growth modulation may still be appropriate to reduce deformity in high-risk patients. Level of Evidence: Level III.